Socio-educational practices in the juvenile criminal justice system in Mexico (Revista Innova Educación, 2024)
In Mexico, adolescents in conflict with the law have the right to receive an education. The educational services offered stem from a policy of the Criminal Justice System (SJP), which introduced changes to the National Law of the Comprehensive Criminal Justice System for Adolescents (LNSIJPA) by adopting a restorative vision of justice and developing measures that contribute to social reintegration. This article analyzes the pedagogical practices of a group of teachers working at a Social Reintegration Center for Adolescent Offenders (CERSAI). The research was qualitative, including semi-structured interviews and focus groups with teachers and key individuals in the institution. Some findings indicate recognition of the objectives and benefits of social reintegration and the potential of the Educational Model for Adolescents in the Criminal Justice System (MEASJP). Teachers encourage adolescents to study, design participatory strategies, and foster peer-to-peer pedagogical exchanges; a high professional profile was observed, but with limited training in juvenile justice issues. They noted a lack of resources, problems with coordination and planning, and inconsistencies between the ideal of a rights-based perspective and the effectiveness of the educational treatment provided. It is concluded that the strategies used in the development of pedagogical practices, as well as the institutional, relational, and practical challenges, must be addressed with commitment. Many changes and proposals in the law are still far from being consolidated, and it is necessary to continue working to improve an education that contributes to the social reintegration of these adolescents.
Keywords: adolescent; criminal sanction; pedagogical practice; reintegration; right to justice